Warming-induced upslope advance of subalpine forest is severely limited by geomorphic processes. - Macias-Fauria, M; Johnson, E (National Academy of Sciences, 2013)
Forests are expected to expand into alpine areas because of climate warming, causing land-cover change and fragmentation of alpine habitats. However, this expansion will only occur if the present upper treeline is limited by low-growing season temperatures that reduce plant growth. This temperature limitation has not been quantified at a landscape scale. Here, we show that temperature alone cannot realistically explain high-elevation tree cover over a >100-km(2) area in the Canadian Rockies and that geologic/geomorphic processes are fundamental to understanding the heterogeneous landscape distribution of trees. Furthermore, upslope tree advance in a warmer scenario will be severely limited by availability of sites with adequate geomorphic/topographic characteristics. Our results imply that landscape-to-regional scale projections of warming-induced, high-elevation forest advance into alpine areas should not be based solely on temperature-sensitive, site-specific upper-treeline studies but also on geomorphic processes that control tree occurrence at long (centuries/millennia) timescales.